An overview of recent advances in state-of-the-art techniques in the demulsification of crude oil emulsions - Saad, M. A.; Kamil, Mohammed; Nour, A. H.; Yunus, R. M.; Awad, Omar I. (MDPI AG, 2019)
The processing of crude oil often requires the extraction of a large amount of water. Frequently, crude oil is mixed with water to form water-in-crude oil emulsions as the result of factors such as high shear at the production wellhead and surface-active substances that are naturally present in crude oil. These emulsions are undesirable and require demulsification to remove the dispersed water and associated inorganic salts in order to meet production and transportation specifications. Additionally, the demulsification of these crude oil emulsions mitigates corrosion and catalyst poisoning and invariably maximizes the overall profitability of crude oil production. Recently, there has been growing research interest in developing workable solutions to the difficulties associated with transporting and refining crude oil emulsions and the restrictions on produced water discharge. Therefore, this paper reviews the recent research efforts on state-of-the-art demulsification techniques. First, an overview of crude oil emulsion types, formation, and stability is presented. Then, the parameters and mechanisms of emulsification formation and different demulsification techniques are extensively examined. It is worth noting that the efficiency of each of these techniques is dependent on the operating parameters and their interplay. Moreover, a more effective demulsification process could be attained by leveraging synergistic effects by combining one or more of these techniques. Finally, this literature review then culminates with propositions for future research. Therefore, the findings of this study can help for a better understanding of the formation and mechanisms of the various demulsification methods of crude oil to work on the development of green demulsifiers by different sources.